Gonyaulax geomunensis sp. nov. and two allied species (Gonyaulacales, Dinophyceae) from Korean coastal waters and East China Sea: morphology, phylogeny and growth response to changes in temperature and salinity. Issue 1 (2nd January 2023) - Kim, Hyun Jung; Li, Zhun; Gu, Haifeng; Mertens, Kenneth Neil; Yeon Youn, Joo; Yoon Kwak, Kyeong; Oh, Seok-Jin; Shin, Kyoungsoon; Yoo, Yeong Du; Lee, Wonchoel; Shin, Hyeon Ho
ABSTRACT: Six strains of three different Gonyaulax species were established by isolating cells from the Korean coastal area and the East China Sea, and their morphologies and molecular phylogenies based on SSU and LSU rRNA gene sequences were examined. In addition, the growth responses of the Gonyaulax species to changes in temperature and salinity were investigated. Based on morphological features and phylogenetic positions, Gonyaulax whaseongensis and G. polygramma were identified, and G. geomunensis sp. nov . is proposed in this study. These species displayed the plate formula typical for Gonyaulax, but G. polygramma and G. geomunensis sometimes showed a small intercalary plate (1a) surrounded by plates 2', *3' and 3''. G. geomunensis was morphologically characterized by an S-type ventral organization, descending with a displacement of one cingulum width and bearing one, two or three prominent antapical spines of similar size. The cell surface, which was distinct from other Gonyaulax species, was thick and heavily reticulated into numerous polygonal areas. The reticulation was deeply excavated. The phylogenetics revealed that G. geomunensis and G. whaseongensis belong to different clades, and that there are two ribotypes of G. polygramma, which were morphologically indistinguishable. These species had a close phylogenetic relationship to G. hyalina, and all of them were characterized by dextral torsion. G. whaseongensis, G. polygramma and G. geomunensis had different growth responses to changes of temperature and salinity, respectively, indicating that morphological and phylogenetic identification of Gonyaulax species can be supported by ecological niches.